The metaphysics of light in hexaemeral literature: from Philo of Alexandria to Gregory of Nyssa - Katsos, Isidoros (Oxford early Christian studies, 2023)
This volume critically re-evaluates the received interpretation of the nature of light in the ancient sources. The view that vision had priority over light is rejected in favour of a luminocentric reading of philosophical and theological cosmology in late antiquity.